“O significado das ligas acadêmicas para estudantes de medicina” - Canôas, Walter Swain (2016)
Introduction: Academic leagues have an important educational space that has been gradually expanding; coinciding with the curricular reformation period in FCMS/PUC-SP. Not much is known or has been studied about its meaning and the students’ perceptions about their participations in said academic leagues. Objectives: To analyze the significance and perception of academic leagues on the medicine major for students that attend FCMS / PUC-SP at Campus-Sorocaba. To analyze the meaning and significance of these leagues in the teaching-learning process of medicine students and of the academic medical league programs. To verify involved students’ perceptions about the academic leagues and their role in academically based education. Methods: The studied population included medical students enrolled in FCMS / PUC-SP’s program that are already partaking in said academic leagues. In addition, an open question test was applied, as well as an invitation to take part in a focus group was made. The data was analyzed through a content analysis method. Results: The categories studied, based on an interview proposed to the student group, show the importance of academic leagues for the medicine major as a source of theoretical and practical knowledge, and also, as an introduction into the medical, social, institutional and academic environments. Students seek these leagues as a way to approach, rapidly, the medical profession, and to learn medical specialties and deepen their curricular themes with theoretical lessons. Conclusion: Students seek personal development and the access to topics of interest regarding their studies, finding in academic leagues an environment in which they can address questions regarding their gaps in knowledge, professional inquiries, as well as academic and social bonds. Even though there is not a suitable assessment of its role in an education program, being part of these leagues seems to be advantageous to the students